The Impact of Integrated and Separate Meta-Affective and Meta-Cognitive-Based Training on Students’ Reconciling Tensions and Dilemmas Competency in Science Learning - Rusyati, Lilit; Nuryani Y. Rustaman; Ari Widodo; Minsu Ha (Jurnal Serambi Ilmu, 2024)
In a world marked by inequity, young people will be required to become adept at balancing tensions, dilemmas, and trade-offs, such as balancing equity and freedom, autonomy and community, innovation and continuity, and efficiency and the democratic process, in local settings with sometimes global implications. This study uses The Static-Group Pretest-Posttest Design. There are 50 students in integrated training and 50 students in separate training who are in the 7th, 8th, and 9th grades. Teachers frequently guide students in the use of meta-affective and meta-cognitive strategies during the science learning process in integrated training, whereas researchers train students in the interpretation and independent use of meta-affective and meta-cognitive strategies during separate science learning. The instrument used was a questionnaire with five Likert scales (1 = not at all typical of me, 2 = not very typical of me, 3 = somewhat typical of me, 4 = fairly typical of me, and 5 = very typical of me). The competence of "reconciling tensions and dilemmas" is constructing with four indicators, namely integrated way, inter-relations, logics and positions, and perspectives. Based on general data for all grades, students who received meta-affective and meta-cognitive training separately from science learning experienced an increase. Meanwhile only one indicator namely logics and positions is positive changes in integrated meta-affective and meta-cognitive-based training. This shows that students can think and carry out activities in various ways to understand science independently, without having to be guided by the teacher.